The Model of a Second-Hand Goods Resale Exchange under Transactional Pricing Strategy - Iarmolenko, Iuliia; Chornous, Galyna (Ekonomika, 2020)
A modern effective business model involves the use of an appropriate pricing strategy. However, not only a short-term profitability matters but also long-term clients’ loyalty. The main purpose of this paper is to present a specific transactional pricing strategy for a second-hand goods resale exchange platform, which allows to avoid possible negative outcomes of being associated with consumer discrimination. Using simulation modeling approach, it was shown how customer segmentation combined with transactional pricing can help to gain higher profitability. The model is based on the work of intelligent agents that recreate the full product lifecycle. Changing the input parameters of the model, it is possible to simulate different scenarios of a company’s activity and market conditions. The model supports the inclusion of any number of products, while its intelligent agents’ methods are still flexible to replace with other techniques. The simulation model has shown that the use of transactional pricing can increase the profitability of a business, while keeping its clients loyal.